Vibration Controlled Transient Elastography (Fibroscan®) in sickle cell liver disease ‐ could we strike while the liver is hard?. (19th June 2019) - Ben Yakov, Gil; Sharma, Disha; Alao, Hawwa; Surana, Pallavi; Kapuria, Devika; Etzion, Ohad; Hsieh, Matthew M.; Tisdale, John F.; Fitzhugh, Courtney D.; Kleiner, David E.; Levy, Elliot B.; Chang, Richard; et al.
Summary: Vibration controlled transient elastography (VCTE) is validated for the evaluation of hepatic fibrosis in different liver diseases. Sickle cell liver disease (SCLD) results from a cumulative hepatic injury and its lifelong and progressive nature raises the need for a non‐invasive tool for fibrosis evaluation. Fifty patients, aged between 23 and 59 years with sickle cell disease and suspected SCLD underwent a VCTE followed by a liver biopsy. Biopsies were evaluated for various scores of liver disease that were then correlated to VCTE score. 90% of our patients had an Ishak Fibrosis (IF) score between 0–2 (Group A‐minimal to no fibrosis) and 10% of the patients had IF score between 3–6 (Group B‐advanced fibrosis). The median Transient Elastography (TE) for patients in Groups A and B was 4·8 kilopascals (kPa) and 17·6 kPa, respectively. A positive correlation was shown between TE and IF score, R  = 0·0·68 ( P  = <0·0001); a positive correlation was also shown with Histology Activity Index fibrosis score, R  = 0·64 ( P  = <0·0001). This study emphasises the need for further studies of non‐invasive tools and their utility in liver fibrosis evaluation of patients with SCLD.